(3EceGd JgPjH GdceGd aj CSeGA GdQLGds - (3oenZrdWGj Hf nbpdjL Hf YHO Gddg GdHcLQj GdeUQj GdMcQj GdMfaj, CHh YHO Gddg, YdGA GdOjf , J (B762 (3g` s; (3GdMGaX GdeRj , jhSa Hf YHO GdQMef Hf jhSa LeGd GdOjf GdRcj CHh eMeO GdbVGYj GdcdHj, LeGd GdOjf CHh GdMLGL GdMGaX GdeRj,J (B742 (3g` s
(3ChdgG (B:s
(3ESeGYjd Hf eMeO Hf MLGQI GdEjGei s
(3BNQgG (B:s
(3SYjO Hf OGhO Hf RjQ GdeOfji s
(3fSNI KGdKIs
(3hGdehLhO efg eLdO eVWQH GdChQGb jTJed Ydi HYV CLRGA ef JLRFI GdCUds
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3JPjjds
Keywords: (3GdJGQjNs